2012
DOI: 10.1038/leu.2012.4
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting inhibitor of apoptosis proteins as therapeutic targets in hematological malignancies

Abstract: Resistance to apoptosis is one of the hallmarks of human cancers and contributes to the insensitivity of many cancers to commonly used treatment approaches. Inhibitor of apoptosis (IAP) proteins, a family of anti-apoptotic proteins, have an important role in evasion of apoptosis, as they can both block apoptosis-signaling pathways and promote survival. High expression of IAP proteins is observed in multiple cancers, including hematological malignancies, and has been associated with unfavorable prognosis and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 110 publications
(164 reference statements)
1
28
0
Order By: Relevance
“…High expression levels of IAP proteins including XIAP and cIAP2 have been linked to poor prognosis in AML in several independent studies [8][9][10]12,27]. Furthermore, we demonstrated that Smac mimetic sensitizes AML cell lines and primary AML samples for cytarabineinduced cell death [16].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…High expression levels of IAP proteins including XIAP and cIAP2 have been linked to poor prognosis in AML in several independent studies [8][9][10]12,27]. Furthermore, we demonstrated that Smac mimetic sensitizes AML cell lines and primary AML samples for cytarabineinduced cell death [16].…”
Section: Discussionmentioning
confidence: 92%
“…Consistently, treatment with BV6/HDACI/zVAD.fmk Second, Smac mimetic in combination with HDACIs may pave the avenue to more effective treatment options to overcome evasion of apoptosis in AML by triggering necroptosis as an alternative cell death program. Treatment resistance of AML is often caused by the inability of cells to undergo apoptosis [27], thus underlining the significance of necroptosis induction by Smac mimetic/HDACIs combination therapy in order to bypass evasion of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,15 In the last decade, several research efforts were exerted to develop new small molecules mimicking SMAC activity for the use in cancer therapy. [16][17][18][19][20] Interestingly, recent studies have shown the ability of SMAC mimetics to induce degradation of cIAPs, leading to activation of the noncanonical NF-kB pathway and TNF-dependant apoptosis. 21,22 Moreover, there are several ongoing clinical studies to prove the antitumor efficacy of SMAC mimetics either alone or in combination with chemotherapy in different tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of cancer cells to evade apoptosis can be induced by a range of different alterations including physiological changes such as activation/upregulation of mitogenic signalling pathways (i.e. MAPK, Akt) or inactivation/downregulation of certain apoptotic molecules [66]. The anti-apoptotic IAPs have an important role in helping cancer cells evade apoptosis, as they can both block apoptosis signalling pathways and promote survival [66,67].…”
Section: Resistance To Apoptosis: Autophagy As a Survival Processmentioning
confidence: 99%